Neoadjuvant or adjuvant sirolimus for malignant metastatic or locally advanced perivascular epithelioid cell tumors: two case reports. Issue 3 (March 2016) - Batereau, Christiane; Knösel, Thomas; Angele, Martin; Dürr, Hans Roland; D'Anastasi, Melvin; Kampmann, Eric; Ismann, Bernhard; Bücklein, Veit; Lindner, Lars H.
Abstract : Perivascular epithelioid cell tumors (PEComas) are very rare mesenchymal tumors, characterized by the presence of perivascular epithelioid cells. Despite their often benign nature, malignant variants with a locally aggressive growth pattern and even distant metastases are known. We describe two cases of malignant PEComas. The first patient had an extensive peritoneal spread and a history of multiple resections, and received the mechanistic target of rapamycin inhibitor sirolimus in a postoperative setting as maintenance therapy. The second patient presented with locally advanced disease in the iliac fossa and was treated with sirolimus in a neoadjuvant setting and achieved complete remission. Both patients have been under treatment for 18 and 52 months, respectively, and are currently in complete remission. These two cases indicate that mechanistic target of rapamycin inhibition for malignant PEComas could be a safe and successful treatment strategy in a neoadjuvant setting with an acceptable toxicity profile.